Sources of Contagion : Finance or Trade? (IMF Working Papers; Working Paper ;, 1999)
This paper presents evidence that spillovers through bank lending, as opposed to trade linkages and country characteristics, can help explain contagion. We construct a measure of competition for bank funds and find evidence in favor of a common lender effect in the Mexican, Thai, and Russian crises, after controlling for macroeconomic fundamentals. The results are quite robust to the definition of the finance indicator. In the case of the Asian crisis, results are not always robust to the inclusion of trade competition, reflecting the high correlation between competition for funds and trade.